Academic Historians in Canada Report Both Positive and Negative Attitudes Towards E-books for Teaching and Research - Coates, Heather (Evidence Based Library and Information Practice, 2013)
Objective – To understand academic historians’ attitudes towards, and perceptions of, e-books for use in teaching and research. Design – Qualitative analysis of semi-structured interviews using a grounded theory approach. Subjects – Ten faculty members in departments of history at academic institutions in Southwestern Ontario participated. Methods – Participants were recruited using flyers and email distribution lists. The authors conducted semi-structured interviews lasting 30-60 minutes, between October 2010 and December 2011. After 10 interviews, the authors determined saturation had been reached and ceased recruitment. Interviews were recorded and transcribed for coding. Analysis was conducted using grounded theory procedures incorporating Roger’s Innovation decision model. Main Results – The authors elicited participants' perceptions of e-books without providing a common definition for the concept. Consistent with previous studies, participants were confused about what constituted an e-book, particularly the distinction between e-books and electronic journals and databases. Several comments included illustrate this confusion, indicating the responses collected may represent perceptions of e-resources more generally, rather than e-books in particular. The authors mention that at least one participant who initially responded that they had not used e-books later changed their response as the interview progressed. Unfortunately, the exact number of participants who did so is not reported. Participants reported both negative and positive attitudes towards e-books. Attitudes varied depending on the characteristic discussed. The characteristics identified focused primarily on the delivery mechanism, rather than the content, of e-books. The authors identified four factors each as contributing to positive and negative attitudes. Factors associated with a negative attitude included availability, serendipity, cost, and tradition. These factors stemmed from concerns about changing student research behaviours resulting from the differences between e-books and print books. Factors associated with a positive attitude included convenience, teaching innovations, research practices, and cost benefits. These factors largely reflected benefits to students, such as the ability to access e-books easily (convenience), increased access in general, and the perceived relatively low cost of student e-books. The factor directly benefitting respondents was improved speed and accuracy in their work, enabled by particular technological features. While participants were eager to use e-books in the classroom, there were concerns about implications for research practices. Participants worried that the benefits of browsing and serendipitous discovery would be lost as students chose materials based on convenience rather than other factors, such as quality. Finally, the perceived lack of digitized historical documents available for use as primary sources was also of concern. Conclusions – The authors state that confusion regarding the nature of e-books slows adoption. While participants were exploring ways to incorporate e-books into their norms, values, and research practices, they are unlikely to rely solely on e-books as primary sources. This stems from two perceptions. First, current e-book formats and platforms do not authentically represent all the characteristics of print books. Second, there are insufficient primary sources available as e-books. The validity of these perceptions is not addressed in this article.